2014
DOI: 10.5120/15866-4804
|View full text |Cite
|
Sign up to set email alerts
|

North Indian Classical Music's Singer Identification by Timbre Recognition using MIR Toolbox

Abstract: Timbre recognition has always been associated with musical instrument identification. In music information retrieval (MIR) community there has always been increasing interest in identifying singers and identifying the musical instruments. There can be unending debate on, whether to consider human throat as a kind of musical instrument generating sound through air pressure and vibration or not. Any musical sound possesses "Timbre", an unidentified and undefined entity which is yet non-tangible that uniquely def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Carnatic singer identification was proposed for six singers by Sridhar and Geetha [29] for efficient music retrieval of Carnaticbased songs. Saurabh et al [30] identified ten singers from North Indian classical music using timbre descriptors for noise-free studio recordings accompanied with continuous background music of tanpura and violin/harmonium/flute, etc., and achieved an accuracy of 58.33%. A technique of identifying singers using video songs from the Internet and CD for Indian playback singers using cepstral coefficients is presented in [31,32], however tested for a lower corpus.…”
Section: Related Workmentioning
confidence: 99%
“…Carnatic singer identification was proposed for six singers by Sridhar and Geetha [29] for efficient music retrieval of Carnaticbased songs. Saurabh et al [30] identified ten singers from North Indian classical music using timbre descriptors for noise-free studio recordings accompanied with continuous background music of tanpura and violin/harmonium/flute, etc., and achieved an accuracy of 58.33%. A technique of identifying singers using video songs from the Internet and CD for Indian playback singers using cepstral coefficients is presented in [31,32], however tested for a lower corpus.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, the development of a music emotion analysis system is a challenge for researchers today, especially research on non-western music since many research works 2 are still based on western music. We found a few non-western works such as Sinhala (Sri Lanka) songs [2] and Indian (India) songs [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is used to determine whether a random variable comes from a population which is normally distributed (Shenoy et al, 1994). For experiment purpose 5 Musical features or Audio features like spectral centroid, entropy, skewness, kurtosis and brightness are used as a dataset (mahto et al, 2014;Datta et al, 2017;Chandwadkar et al, 2013;Deshmukh et al, 2014;Masood et al, 2016). Normality test or (Kolmogorov-Smirnov test) is proposed on spectral centroid, entropy, skewness, kurtosis and brightness, concerning a singer's voice.…”
Section: Introductionmentioning
confidence: 99%